Communicable Diseases Intelligence volume 3 issue 4 - 2 March 1979 - whole issue - No author listed, (Communicable Diseases Intelligence, 1979)
Whole-issue pdf, comprising: Virus reports this period [Amendments to Bulletin 79/4 as advised in CDI 79/5, page 3] "The influenza A. isolate described on page 1 was described as an "important" infection. This should have read "imported". This isolate has now been serologically confined as Influenza A/USSR/90/77 (seroconversion 1:10 to 1:160)." "The reporting period for the issue should have read 8 February 1979 to 21 February 1979." [end] Article Genital vaccinia. [Melbourne, VIC.] B-lactamase producing N. gonorrhoeae. "A further 10 isolates of the above organism have been reported in Australia since the beginning of the year. These are:..." [continues...] [amendment in Issue 5 page 3] Vaccination failures. "In Bulletin 79/2, a request was made for information on cases of measles in which the patient had a fully documented measles vaccination history. Information was received, but the request is reiterated, this time with an emphasis on an invitation for data describing the frequency of such failures in the community." [continued...] Salmonella isolates. "The monthly inclusion of salmonella tables as in 1978, will be varied this year. Routine reporting will list only the totals for each serotype for the month, and detailed summaries will be included periodically." [continued...] Australia - Communicable Diseases Intelligence Reporting Period - 08/02/1979 to 28/02/1979 Bulletin Number 79/4